If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1 + -1x) = 2(1 + -3x) (1 * 7 + -1x * 7) = 2(1 + -3x) (7 + -7x) = 2(1 + -3x) 7 + -7x = (1 * 2 + -3x * 2) 7 + -7x = (2 + -6x) Solving 7 + -7x = 2 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 7 + -7x + 6x = 2 + -6x + 6x Combine like terms: -7x + 6x = -1x 7 + -1x = 2 + -6x + 6x Combine like terms: -6x + 6x = 0 7 + -1x = 2 + 0 7 + -1x = 2 Add '-7' to each side of the equation. 7 + -7 + -1x = 2 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 2 + -7 -1x = 2 + -7 Combine like terms: 2 + -7 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 6x-3(5x+3)=17 | | (-2)-3+2= | | 0.08-0.2x=1.32 | | 42y+43+53=180 | | 0=x*x+7x+12 | | 14r=98 | | 3p^2+10p+7= | | 100+30+2y=180 | | h(x)=2x^2+3x+1 | | 2x-4=-4x+6 | | 4(3v-2)=8(2w+3) | | 3x+8=-x+12 | | 3y-11=-3 | | 65+73+7x=180 | | 2t^2+11t+9= | | M^2-6m-85=6 | | 2y^2+y+11=0 | | 76+68+3u=180 | | 3v^2+5v+2= | | 59=54y | | 6x=8+15y | | -x+3=-4x-6 | | Y=3x^2-115+444 | | -1.5x+6= | | 2(3x+5)=21 | | x+56=28 | | 47+7z+12z=180 | | -9n+(n-7)=6n-231 | | -30=-2(-1n+3) | | P^3+4p^2+8p+32=0 | | 9y=7y+8 | | -y-2(2y-1)=5(1-y) |